An Analysis of Grammatical Errors Among High School Students at Perguruan Panglima Polem Rantauprapat - Jennifer Carren; Ivana Ivana; Jessy Jessy (Jurnal Indonesia Sosial Sains, 2026)
This study aims to analyze the misuse of Chinese structural particles, namely 的 (de), 地 (de), and 得 (de) in students of Panglima Polem Rantau Prapat College. These particles have different grammatical functions, but in practice learning often cause confusion for Chinese learners. The research method used is a qualitative descriptive method with data collection techniques in the form of written tests and analysis of student answer results. The results of the study show that the error of using particles is still quite high. The most common mistakes occur in the use  of 的 and 地 because students have not understood the difference in functions between attributive and adverbial ones. In addition, some students are also still mistaken in using 得 as a complementary marker of results and degrees. Factors that cause errors include lack of grammatical understanding, the influence of mother tongue, and lack of contextual practice. This research is expected to contribute to Chinese language learning, especially as an evaluation material for teachers in determining particle teaching strategies so that they are more effective and easy to understand by students.